CULTURAL SYNERGITY AND ISLAMIC EDUCATION NATIONAL CHARACTER FORMATION - Hadirman, Hadirman (Lafadz Jaya Publisher, 2022)
This paper aims to determine the synergy of culture, Islamic education and national character development. Culture is the first step in shaping the character of students (younger generations) from the perspective of the people who own the culture. Meanwhile, Islamic education forms the character of students (younger generations) through the transmission of knowledge based on the values of universality of Islamic education and learning interactions. Thus, the two of them can create synergy to shape the character of the nation for students (younger generations) in the future.